The Influence Of Work Motivation And Work Environment On The Performance Of Educational Personnel With Religiosity As Moderation At The Kiai Haji Achmad Siddiq State Islamic University, Jember Regency - Rizna Ramadhani Winanda; Muhadjir Anwar; Hesty Prima Rini (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
This study aims to assess the impact of work environment motivation on the performance of teaching staff at UIN KHAS Jember. A higher education institution is considered a knowledge carrier and learning institution with high hopes and goals, a scientifically developed Forum to provide ethical and skills guidance to students and academics. This study uses the causality method with a causal relationship between the positions of the research variables and the influence of the independent variables on the dependent variable. Based on the results obtained, work motivation can positively impact performance. This indicates that the reason increased by the employees' leadership will affect increasing motivation. The results of the path coefficient indicate that the relationship between fellow employees has a significant role in carrying out social relations with many people. It will create a sense of security and make you feel acknowledged by others. The work environment positively influences the performance of UIN Khas Jember's academic staff, which indicates that a good work environment can produce high-performance levels, thereby indirectly causing employees to work at optimal levels.